(untitled) (Medico Legal Update, 2020)
Measurement of chest expansion is one of the important steps in clinical examination of respiratory system and this can be done by chest palpation with hands or more accurately by using of tape measure. Assessment of chest expansion can give an important idea about different disorders in the thoracic cage or in the lung itself by detection of any limitation of chest expansion. Also it used for evaluation of progression and treatment response of many pulmonary, neurological and rheumatological diseases. In number of famous clinical text books the lower normal limit of chest expansion is 5 cm but we suggest that the reference range of chest expansion is varied in different races. In this study 130 healthy non smoker volunteers living in al-Muthanna governorate, 65 females(50%) and 65 males(50%), were involved by measuring of their chest expansion with tape measure at level of the fourth intercostal space for two times and best reading was taken for each participant. The body weight of the participants in this study range from 52 kg to 86 kg in females and from 50 kg to 90 kg in males. According to this study normal range of chest expansion was(2-5 cm) (mean=3.35cm,SD=0.685) for females and (2 - 5.5cm)(mean=3.38 cm, SD=0.734) for males where the best result was in athletics. There is age wise reduction of chest expansion for both male and female where the mean chest expansion in 18-34 years age group is 3.74 cm for female and 3.72 for male, in 35-64 years age group is 3.57 cm for female and 3.66 cm for male and in those of 65 years and more is 2.63 cm for female and 2.66 for male. So the chest expansion lower normal limit of participants in this study (as sample of Iraqi people) is vary from other reference ranges. This can be explained by the difference of life style and genetic factors between societies and we should not depend on same reference range for chest expansion in deferent races.